2007
DOI: 10.1038/bdj.2007.571
|View full text |Cite
|
Sign up to set email alerts
|

An audit of 600 referrals to a primary care based oral surgery service

Abstract: Acknowledging the small sample, it was safe and effective to diagnose and treat a broad spectrum of patients and oral surgical problems in the primary health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…The fi ndings are consistent with earlier research which reported satisfaction with oral surgery provided in primary care. 8,9 Bell 8 and Clark 9 cited various reasons for this, including a simplifi ed appointment process, shorter waiting times, familiarity and personal nature of the service and their geographical convenience, which are consistent with the fi ndings reported here. However, patient satisfaction surveys often report high levels of satisfaction, even when further investigation reveals dissatisfaction with aspects of a service.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The fi ndings are consistent with earlier research which reported satisfaction with oral surgery provided in primary care. 8,9 Bell 8 and Clark 9 cited various reasons for this, including a simplifi ed appointment process, shorter waiting times, familiarity and personal nature of the service and their geographical convenience, which are consistent with the fi ndings reported here. However, patient satisfaction surveys often report high levels of satisfaction, even when further investigation reveals dissatisfaction with aspects of a service.…”
Section: Resultssupporting
confidence: 83%
“…Although the proportion of each procedure undertaken differed, the case-mix and fi ndings are similar to those reported earlier. [7][8][9][10] Overall 12.7% patients did not attend appointments and 11.6% of those who attended were not treated after their initial appointment. Although the reasons for patients not proceeding to treatment were recorded (Table 1), nothing is known of the reasons for failed attendance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kendall provided one of two such descriptions of how a Level 2 provider might work 14 and this is described below, while Bell describes a retrospective audit of a primary care scheme designed to address issues in provision of services to remote areas. 16 Utilising two GDP practices in the Croydon area, combined with a simple referral management system, all non-urgent referrals for oral surgery procedures were captured and then subjected to a two-stage triage process. The first was an administrative check of the paper referral form and the second was a clinical assessment of a patient's suitability for primary care treatment.…”
Section: Primary Care (Level 2) Servicesmentioning
confidence: 99%